3D hierarchical structure hard carbon material and preparation method and application thereof

The 3D graded hard carbon material with a particle size of 2 to 40 μm was prepared by microsuspension polymerization, which solved the shortcomings of the particle size of less than 1 μm in the prior art, and achieved both high exposure of the material and large-scale filtration.

CN119683600AActive Publication Date: 2025-03-25DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311236563.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-03-25
Estimated Expiration
2043-09-22

AI Technical Summary

Technical Problem

In the prior art, the particle size of the 3D hierarchical polystyrene-based carbon material synthesized by hydrothermal method is less than 1 μm, making it difficult to meet the needs of large-scale filtration.

Method used

By adopting the micro-suspended polymerization method, a 3D graded structure hard carbon material with uniform size is prepared by adding emulsifier, stabilizer, polyvinyl alcohol and water to the mixed liquid, divinylbenzene, styrene, pore-generating agent and initiator, the particle size on the 3D scale is controlled to be greater than 1 μm.

Benefits of technology

A 3D graded hard carbon material with a particle size of 2 to 40 μm was prepared, which maintains high exposure to the material while increasing the particle size, which facilitates separation, and overcomes the shortcomings of particle size less than 1 μm in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683600A_ABST
    Figure CN119683600A_ABST
Patent Text Reader

Abstract

The invention discloses a 3D hierarchical structure hard carbon material and a preparation method and application thereof.The preparation method comprises the following steps that S1, divinylbenzene, styrene, a pore-foaming agent and an initiator are added into a mixed solution containing an emulsifier, a stabilizer, polyvinyl alcohol and water, and turbid liquid is obtained; s2, heating the turbid liquid obtained in the step S1 for reaction to obtain a styrene-diethylene benzene copolymer; and S3, pre-oxidizing and carbonizing the styrene-diethylene benzene copolymer obtained in the step S2 to obtain the hard carbon material with the 3D hierarchical structure. 3D graded polystyrene-based carbon flower-shaped microspheres with uniform sizes of 2-40 [mu] m are prepared through a micro-suspension polymerization method, and the particle size is increased while high exposure of the material is maintained, so that separation is facilitated. The problems that in the prior art, the particle size of a polystyrene-based carbon material with a 3D hierarchical structure synthesized through a hydrothermal method is smaller than 1 micron, and large-scale filtration is not facilitated are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a 3D hierarchical structure hard carbon material and a preparation method and application thereof, belonging to the technical field of hard carbon materials. Background Art

[0002] Since 3D hierarchical carbon materials can prevent the stacking of low-dimensional modules, they can not only shorten the diffusion distance of substances or charges, but also greatly expose active sites to achieve high activity, durability and high efficiency catalysis, which has been widely studied in the field of energy and catalysis. The 3D hierarchical structure composed of low-dimensional building blocks such as 0D, 1D and 2D structures can not only inherit the original properties of the material, but also bring unexpected superior performance. At present, hierarchical flower-shaped, sea urchin-shaped and array carbon materials can be prepared. The commonly used methods are (i) hydrothermal method, (ii) template method, (iii) nanoemulsion assembly, (iv) spatial confinement assembly, (v) modular self-assembly and (vi) direct ink writing. "Monomicellar assembly to synthesize structured and functional mesoporous carbonaceous nanomaterials." Zhao Dongyuan's team uses the method of single-molecule micelle self-assembly to prepare a variety of hierarchical mesoporous carbonaceous materials with a particle size of less than 200nm; CN110252160A discloses a mixed matrix gas separation membrane material containing 3D flower-like carbon materials and a preparation method, using a solvent thermal method to synthesize 3D flower-like carbon materials with polyimide as a raw material, with a particle size of 700nm; CN106432562B discloses a chloromethylated magnetic polystyrene nanosphere and a preparation method thereof, using ferroferric oxide as a template, and wrapping the outer layer with styrene-p-chlorostyrene copolymer, and using the template method to prepare a multi-component superstructure with a particle size of 20 to 140nm. The 3D hierarchical carbon materials prepared by the above methods are all particles that are usually less than 1μm, and the synthesis steps are complicated, which is not easy to scale up for production. Summary of the invention

[0003] According to one aspect of the present application, a 3D hierarchical hard carbon material is provided, which solves the following technical problems: The common method for large-scale preparation of 3D hierarchical polystyrene-based carbon materials is the hydrothermal method, but the particle size of the 3D hierarchical polystyrene-based carbon material synthesized by the hydrothermal method is less than 1 μm, which is not conducive to large-scale filtration. In order to overcome the above problems, the present application adopts a micro-suspension polymerization method to prepare 3D hierarchical polystyrene-based carbon flower-like microspheres with uniform size in micrometers, while maintaining high exposure of the material, increasing the particle size to facilitate separation.

[0004] This application adopts the following technical solutions:

[0005] A method for preparing a 3D hierarchical structure hard carbon material comprises the following steps:

[0006] S1. Adding divinylbenzene, styrene, a porogen and an initiator to a mixed solution containing an emulsifier, a stabilizer, polyvinyl alcohol and water to obtain a suspension;

[0007] S2, heating the suspension obtained in step S1 to obtain a styrene-divinylbenzene copolymer;

[0008] S3. Pre-oxidize and carbonize the styrene-divinylbenzene copolymer obtained in step S2 to obtain the 3D hierarchical structure hard carbon material.

[0009] The microemulsion polymerization method is used to control the particle size on the 3D scale to be larger than 1um, and the emulsifier and stabilizer are used as a mixed emulsifier to control the morphology on the low-dimensional scale, thereby obtaining a resin material with a 3D hierarchical structure at a micron particle size.

[0010] Optionally, in step S1, the molecular weight of the polyvinyl alcohol is 70,000-114,400.

[0011] Optionally, in step S1, the emulsifier is selected from at least one of OP-10, TX-10, NP-10, and Peregal O-10.

[0012] Optionally, in step S1, the weight ratio of the emulsifier to styrene is 0.2 to 0.4:1.

[0013] Optionally, in step S1, the stabilizer is selected from at least one of sodium dodecyl sulfate and sodium alginate.

[0014] Optionally, in step S1, the weight ratio of the stabilizer to styrene is 0.1-0.2:1.

[0015] Optionally, in step S1, the weight ratio of polyvinyl alcohol to styrene is 0.05 to 0.1:1.

[0016] Optionally, in step S1, the weight ratio of water to styrene is 3 to 15:1.

[0017] Optionally, in step S1, the porogen is selected from C6 to C 15 At least one of the liquid alkanes, the porogen is selected from a liquid alkane having a boiling point greater than 120°C.

[0018] Optionally, in step S1, the weight ratio of the porogen to styrene is 1.5 to 2.5:1.

[0019] Optionally, the porogen is selected from at least one of dodecane, tridecane and tetradecane.

[0020] Optionally, in step S1, the initiator is selected from at least one of benzoyl peroxide, azobisisobutyronitrile, and lauryl peroxide.

[0021] Optionally, in step S1, the mass content ratio of the initiator to styrene is 0.01 to 0.01:1.

[0022] Optionally, in step S1, the weight ratio of divinylbenzene to styrene is 0.6 to 2:1.

[0023] Optionally, in step S2, the heating reaction includes stage I, stage II, and stage III.

[0024] The reaction conditions of the stage I are: reaction temperature of 65-72° C., and reaction time of 1 h-4 h.

[0025] The reaction conditions of the stage II are: reaction temperature of 72-78° C., and reaction time of 3 h to 12 h.

[0026] The reaction conditions of the stage III are: reaction temperature of 82-95° C., and reaction time of 8-16 h.

[0027] Optionally, a stage II-1 is further included between the stage II and the stage III, and the reaction conditions of the stage II-1 are: reaction temperature is 78 to 82° C., and reaction time is 0.2 h to 0.8 h.

[0028] Optionally, in step S3, the pre-oxidation conditions include:

[0029] The pre-oxidation is carried out in an oxidizing atmosphere, the pre-oxidation temperature is 60 to 300°C, and the pre-oxidation time is 6 to 10 hours;

[0030] Wherein, the oxidizing atmosphere is oxygen or air;

[0031] Optionally, the heating rate of the pre-oxidation is 3-10° C. / min.

[0032] Optionally, the carbonization conditions include:

[0033] The carbonization process is carried out under an inert gas atmosphere, with a carbonization temperature of 700 to 1600° C., a carbonization time of 0.5 to 10 hours, and a heating rate of 1 to 15° C. / min.

[0034] Optionally, the inert gas atmosphere is selected from at least one of nitrogen, helium and argon.

[0035] According to another aspect of the present application, a 3D hierarchical structure hard carbon material is provided, characterized in that the 3D hierarchical structure hard carbon material is prepared by the above-mentioned preparation method.

[0036] Optionally, the 3D hierarchical hard carbon material is a flower-shaped microsphere having a three-dimensional multi-level structure.

[0037] Optionally, the average particle size of the 3D hierarchical structure hard carbon material is 2 to 40 μm.

[0038] According to another aspect of the present application, there is also provided an application of the above-mentioned 3D hierarchical structure hard carbon material in lithium-ion batteries, sodium-ion batteries, and oxygen reduction electrocatalysts.

[0039] The beneficial effects of this application include:

[0040] The present application provides a method for preparing a 3D hierarchical hard carbon material, which is a method for synthesizing polystyrene-based carbon flower-like microspheres with a 3D hierarchical structure. The 3D hierarchical polystyrene-based carbon flower-like microspheres with a size of 2 to 40 μm are prepared by a microsuspension polymerization method. The particle size is increased while maintaining high exposure of the material to facilitate separation. The average particle size before carbonization is 4 to 60 μm, and the average particle size after carbonization is 2 to 40 μm. The specific surface area is less than 70 m 2 / g, overcoming the problem that the particle size of the polystyrene-based carbon material synthesized by the hydrothermal method in the prior art is less than 1 μm, which is not conducive to large-scale filtration. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a scanning electron microscope photograph of the sample in Example 1, with a scale of 10 μm.

[0042] Figure 2 The scanning electron microscope photograph of the sample in Comparative Example 2 is shown with a scale of 10 μm. DETAILED DESCRIPTION

[0043] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0044] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0045] The commercial brand of polyvinyl alcohol used in the examples is PVA 2488.

[0046] Example 1

[0047] Step 1: Add 1g OP-10 and 1g sodium dodecyl sulfate to 70g 1% polyvinyl alcohol aqueous solution, stir until dissolved, add 6g divinylbenzene, 7g styrene, 10g tridecane and 0.18g benzoyl peroxide mixed solution after removing the inhibitor, heat to 70°C for reaction for 2h, then heat to 75°C for reaction for 4h, then heat to 80°C for reaction for 0.5h, and finally heat to 90°C for reaction for 11h.

[0048] Step 2: After washing and drying, the obtained styrene-diethylenebenzene copolymer is pre-oxidized by heating to 280°C at 6°C / min and maintaining for 2 hours in air. The innovation of this step is as follows: the temperature is slowly raised to 280°C for oxidative crosslinking and evaporation of the porogen.

[0049] Step 3: The pre-oxidized sample was heated to 1400°C at a heating rate of 5°C / min and maintained for 2 hours under a nitrogen atmosphere to obtain a sample. The average particle size of the sample in Example 1 before carbonization was 40 μm, the average particle size after carbonization was 24 μm, and the specific surface area was 24 m 2 / g. SEM morphology pictures are attached. Figure 1 As shown, the particle size distribution is uniform and the graded flower-like structure.

[0050] Example 2

[0051] 2.8g OP-10 and 1.4g sodium dodecyl sulfonate were added to 105g 0.05% polyvinyl alcohol aqueous solution, stirred until dissolved, and then 14g divinyl benzene, 7g styrene, 17.5g tetradecane and 0.7g azobisisobutyronitrile mixed solution were added after the polymerization inhibitor was removed, and the temperature was raised to 70°C for reaction for 2h, then raised to 75°C for reaction for 4h, then raised to 82°C for reaction for 0.2h, and then raised to 90°C for reaction for 11h; after washing and drying, the obtained styrene divinyl benzene copolymer was heated to 300°C at 3°C / min and maintained for 10h under air conditions for pre-oxidation; the pre-oxidized sample was heated to 1400°C at a heating rate of 5°C / min under a nitrogen atmosphere and maintained for 2h to obtain a sample. The structural morphology is similar to that of the sample in Example 1, with uniform particle size distribution and graded flower-like structure, and only the average particle size is different.

[0052] Example 3

[0053] 1.4g of perepin O-10 and 0.7g of sodium dodecyl sulfonate were added to an aqueous solution of 21g of 1.67% polyvinyl alcohol, stirred until dissolved, and then a mixed solution of 4.2g of divinylbenzene, 7g of styrene, 10.5g of tridecane and 0.07g of lauryl peroxide was added, heated to 70°C for reaction for 2h, then heated to 75°C for reaction for 4h, then heated to 80°C for reaction for 0.5h, and then heated to 90°C for reaction for 11h; after washing and drying, the obtained styrene divinylbenzene copolymer was heated to 250°C at 3°C / min and maintained for 10h under air conditions for pre-oxidation; the pre-oxidized sample was heated to 1400°C at a heating rate of 5°C / min under a nitrogen atmosphere and maintained for 2h to obtain a sample. The structural morphology is similar to that of the sample in Example 1, with uniform particle size distribution and graded flower-like structure, and only the average particle size is different.

[0054] Example 4

[0055] 0.7g OP-10, 0.7g TX-10 and 1g sodium alginate were added to 60g 1% polyvinyl alcohol aqueous solution, stirred until dissolved, and then 10g divinyl benzene, 7g styrene, 10g tridecane and 0.11g azobisisobutyronitrile mixed solution were added after the polymerization inhibitor was removed, and the temperature was raised to 70°C for reaction for 2h, then raised to 75°C for reaction for 4h, then raised to 80°C for reaction for 0.5h, and then raised to 90°C for reaction for 11h; after washing and drying, the obtained styrene divinyl benzene copolymer was heated to 250°C at 3°C / min and maintained for 10h under air conditions for pre-oxidation; the pre-oxidized sample was heated to 1400°C at a heating rate of 5°C / min under a nitrogen atmosphere and maintained for 2h to obtain a sample. The structural morphology is similar to that of the sample in Example 1, with uniform particle size distribution and graded flower-like structure, and only the average particle size is different.

[0056] Example 5

[0057] 1g OP-10, 0.7g NP-10 and 1g sodium alginate were added to 70g 1% polyvinyl alcohol aqueous solution, stirred until dissolved, and then 6g divinyl benzene, 7g styrene, 10g n-hexane and 0.11g benzoyl peroxide mixed solution were added, and the temperature was raised to 72°C for reaction for 1h, then raised to 78°C for reaction for 3h, and then raised to 95°C for reaction for 8h; after washing and drying, the obtained styrene divinyl benzene copolymer was pre-oxidized by heating to 60°C at 1°C / min and maintaining for 10h under air conditions; the pre-oxidized sample was heated to 700°C at a heating rate of 1°C / min in a nitrogen atmosphere and maintained for 10h to obtain a sample. The structural morphology is similar to that of the sample in Example 1, with uniform particle size distribution and graded flower-like structure, and only the average particle size is different.

[0058] Example 6

[0059] 1g OP-10 and 1g sodium dodecyl sulfonate were added to 70g 1% polyvinyl alcohol aqueous solution, stirred until dissolved, and then 6g divinyl benzene, 7g styrene, 10g tridecane and 0.18g benzoyl peroxide mixed solution were added after the polymerization inhibitor was removed, and the temperature was raised to 65°C for reaction for 4h, then raised to 72°C for reaction for 12h, then raised to 78°C for reaction for 0.8h, and then raised to 82°C for reaction for 16h. After washing and drying, the obtained styrene divinyl benzene copolymer was pre-oxidized by heating to 300°C at 10°C / min and maintaining for 10h under oxygen conditions; the pre-oxidized sample was heated to 1400°C at a heating rate of 10°C / min in a nitrogen atmosphere and maintained for 2h. The structural morphology is similar to that of the sample in Example 1, with uniform particle size distribution and graded flower-like structure, and only the average particle size is different.

[0060] Example 7

[0061] 1g OP-10 and 1g sodium dodecyl sulfonate were added to 70g 1% polyvinyl alcohol aqueous solution, stirred until dissolved, and then 6g divinyl benzene, 7g styrene, 10g tridecane and 0.18g benzoyl peroxide mixed solution were added after the polymerization inhibitor was removed, and the temperature was raised to 65°C for reaction for 4h, then raised to 72°C for reaction for 12h, then raised to 78°C for reaction for 0.8h, and then raised to 82°C for reaction for 16h. After washing and drying, the obtained styrene divinyl benzene copolymer was pre-oxidized by heating to 300°C at 10°C / min and maintaining for 10h under oxygen conditions; the pre-oxidized sample was heated to 1600°C at a heating rate of 15°C / min in a nitrogen atmosphere and maintained for 2h. The structural morphology is similar to that of the sample in Example 1, with uniform particle size distribution and graded flower-like structure, and only the average particle size is different.

[0062] Comparative Example 1

[0063] 1g OP-10 was added to 70g 1% polyvinyl alcohol aqueous solution, stirred until dissolved, and then a mixed solution of 6g divinylbenzene, 7g styrene, 10g tridecane and 0.18g benzoyl peroxide from which the inhibitor was removed was added, and the temperature was raised to 70°C for reaction for 2h, then raised to 75°C for reaction for 4h, then raised to 80°C for reaction for 0.5h, and then raised to 90°C for reaction for 11h; after washing and drying, the obtained styrene divinylbenzene copolymer was pre-oxidized by heating to 250°C at 3°C / min and maintaining for 10h under air conditions; the pre-oxidized sample was heated to 1400°C at a heating rate of 5°C / min under a nitrogen atmosphere and maintained for 2h to obtain a sample without a specific morphology. This comparative example shows that the absence of a stabilizer will result in the non-production of a secondary structure, thereby causing the dispersed phases to combine with each other to form an inhomogeneous material during the suspension polymerization process.

[0064] Comparative Example 2

[0065] Add 1g of sodium dodecyl sulfonate to 70g of 1% polyvinyl alcohol aqueous solution, stir until dissolved, then add 6g of divinyl benzene, 7g of styrene, 10g of tridecane and 0.18g of benzoyl peroxide mixed solution after removing the inhibitor, heat to 70℃ for reaction for 2h, then heat to 75℃ for reaction for 4h, then heat to 80℃ for reaction for 0.5h, then heat to 90℃ for reaction for 11h; after washing and drying, the obtained styrene divinyl benzene copolymer is pre-oxidized by heating to 250℃ at 3℃ / min and maintaining for 10h in air; the pre-oxidized sample is heated to 1400℃ at a heating rate of 5℃ / min in a nitrogen atmosphere and maintained for 2h to obtain the sample. SEM morphology pictures are shown in the attached Figure 2 As shown, without the addition of non-ionic emulsifier, the obtained morphology only has a low-dimensional structure and does not produce a uniformly distributed particle size.

[0066] Comparative Example 3

[0067] 1g OP-10 and 1g sodium dodecyl sulfate were added to 70g 1% polyvinyl alcohol aqueous solution, stirred until dissolved, and then a mixed solution of 6g divinyl benzene, 7g styrene, 10g solid paraffin and 0.18g benzoyl peroxide from which the inhibitor was removed was added, and the temperature was raised to 80°C for reaction for 4h, and then raised to 95°C for reaction for 12h; after washing and drying, the obtained styrene divinyl benzene copolymer was pre-oxidized by heating to 250°C at 3°C / min and maintaining for 10h in air conditions; the pre-oxidized sample was heated to 1400°C at a heating rate of 5°C / min under a nitrogen atmosphere and maintained for 2h to obtain a sample with no specific morphology, which shows that the reaction conditions and the type of porogen in the polymerization process have a significant effect on the morphology of the polymer.

[0068] Test Example 1

[0069] The samples obtained in Examples 1, 2, 3, 4, 5, 6, and 7 and Comparative Examples 1, 2, and 3 were tested and inspected. The results are shown in Table 1.

[0070] In the battery test, 1M NaClO4 in ethyl carbonate and ethylene fluoride carbonate (1:1) was used as the electrolyte, and the working electrode was composed of active material, Ketjen black and sodium carboxymethyl cellulose in a mass ratio of 7:2:1. The mass loading of active material in the electrode was about 1mg cm-2. Constant current charge and discharge tests were carried out in the range of 0.01-3V.

[0071] Table 1

[0072] <![CDATA[Specific surface area (m 2 / g)]]> Average particle size after carbonization (um) <![CDATA[Specific capacity (mAh g -1 )]]> First effect (%) Example 1 24 24 331.18 94.7 Example 2 15 30 324.48 93.5 Example 3 8 8 334.75 94.5 Example 4 35 21 324.17 92.4 Example 5 46 40 313.14 91.2 Example 6 24 15 335.24 91.3 Example 7 7 2 315.71 95.2 Comparative Example 1 12 65 310.12 88.7 Comparative Example 2 21 20 305.45 84.5 Comparative Example 3 7 12 312.11 84.8

[0073] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing a 3D hierarchical hard carbon material, characterized in that: The steps include: S1. Adding divinylbenzene, styrene, a porogen and an initiator to a mixed solution containing an emulsifier, a stabilizer, polyvinyl alcohol and water to obtain a suspension; S2, heating the suspension obtained in step S1 to obtain a styrene-divinylbenzene copolymer; S3. Pre-oxidize and carbonize the styrene-divinylbenzene copolymer obtained in step S2 to obtain the 3D hierarchical structure hard carbon material.

2. The preparation method according to claim 1, characterized in that: In step S1, the molecular weight of the polyvinyl alcohol is 70000 to 114400; Preferably, in step S1, the emulsifier is selected from at least one of OP-10, TX-10, NP-10, and Peregal O-10; Preferably, in step S1, the weight ratio of the emulsifier to styrene is 0.2 to 0.4:1; Preferably, in step S1, the stabilizer is selected from at least one of sodium dodecyl sulfate and sodium alginate; Preferably, in step S1, the weight ratio of the stabilizer to styrene is 0.1 to 0.2:1; Preferably, in step S1, the weight ratio of polyvinyl alcohol to styrene is 0.05 to 0.1:1; Preferably, in step S1, the weight ratio of water to styrene is 3 to 15:

1.

3. The preparation method according to claim 1, characterized in that: In step S1, the porogen is selected from C6 to C 15 At least one of the liquid alkanes, wherein the porogen is selected from a group having a boiling point greater than 120°C; Preferably, in step S1, the weight ratio of the porogen to styrene is 1.5 to 2.5:1; Preferably, in step S1, the initiator is selected from at least one of benzoyl peroxide, azobisisobutyronitrile, and lauryl peroxide; Preferably, in step S1, the mass content ratio of the initiator to styrene is 0.01 to 0.01:1; Preferably, in step S1, the weight ratio of divinylbenzene to styrene is 0.6 to 2:

1.

4. The preparation method according to claim 1, characterized in that: In step S2, the heating reaction includes stage I, stage II, and stage III; The reaction conditions of the stage I are: reaction temperature of 65-72°C, reaction time of 1h-4h; The reaction conditions of the stage II are: reaction temperature of 72-78°C, reaction time of 3h-12h; The reaction conditions of the stage III are: reaction temperature of 82-95°C, reaction time of 8-16h; Preferably, a stage II-1 is further included between the stage II and the stage III, and the reaction conditions of the stage II-1 are: reaction temperature is 78 to 82° C., and reaction time is 0.2 h to 0.8 h.

5. The preparation method according to claim 1, characterized in that: In step S3, the pre-oxidation conditions include: The pre-oxidation is carried out in an oxidizing atmosphere, the pre-oxidation temperature is 60 to 300°C, and the pre-oxidation time is 6 to 10 hours; Wherein, the oxidizing atmosphere is oxygen or air; Preferably, the heating rate of the pre-oxidation is 3-10° C. / min.

6. The preparation method according to claim 1, characterized in that: The carbonization conditions include: The carbonization process is carried out under an inert gas atmosphere, with a carbonization temperature of 700 to 1600° C., a carbonization time of 0.5 to 10 hours, and a heating rate of 1 to 15° C. / min.

7. A 3D hierarchical hard carbon material, characterized in that: The 3D hierarchical structure hard carbon material is prepared by the preparation method according to any one of claims 1 to 6.

8. The 3D hierarchical hard carbon material according to claim 7, characterized in that: The 3D hierarchical hard carbon material is a flower-shaped microsphere with a three-dimensional multi-level structure.

9. The 3D hierarchical hard carbon material according to claim 7, characterized in that: The average particle size of the 3D hierarchical structure hard carbon material is 2 to 40 μm.

10. Use of the 3D hierarchical hard carbon material according to any one of claims 7 to 9 in lithium ion batteries, sodium ion batteries, and oxygen reduction electrocatalysts.

Citation Information

Patent Citations

  • A chloromethylated magnetic polystyrene nanosphere and its preparation method

    CN106432562B

  • Mixed matrix gas separation membrane material with 3D flower-like carbon material and preparation method thereof

    CN110252160A

  • Synthetic method of novel ordered macroporous-mesoporous-microporous hierarchical porous silicon-aluminium molecular sieve

    CN103979570A

  • Dielectric elastomer composite material and preparation method thereof

    CN114989556A